Construct validity of a clinically correlated knee osteoarthritis ultrasonographic scale: a cross-sectional observational study - Mohamed Mortada; Ghada A Dawa; Youmna A Amer (BMJ Open)
Objectives To assess the validity of a novel ultrasonographic scale for knee osteoarthritis (KOA) and its relation with the degree of pain and clinical features.Design A cross-sectional observational study including 245 patients with knee pain who fulfilled the American College of Rheumatology criteria for KOA. All patients were subjected to clinical assessment Western Ontario and McMaster Universities Index of Osteoarthritis (WOMAC) scale, global visual analogue scale (VAS) and functional assessment through the use of Health Assessment Questionnaire-II (HAQ-II). Ultrasonographic assessment was conducted following ZAGAZIG scale comprising five domains: one for degenerative features (one-third of total score) and the other four for inflammatory features (two-thirds of score).Results There were positive correlations between ZAGAZIG score and all WOMAC subscales (pain, stiffness and function) (r=0.71, p=0.00; r=0.62, p=0.00; r=0.70, p=0.00, respectively).Moreover, there was a strong positive correlation between ZAGAZIG scale and both VAS and HAQ-II (r=0.82, p=0.00 and r=0.67, p=0.00). At cut-off point of >5, total US score distinguishes between patients with KOA with no or mild pain and those with moderate pain (87.2 sensitivity and 87.2 specificity). At cut-off point of 7, total score of ZAGAZIG scale distinguishes between patients with KOA with moderate pain and those with severe pain (94.5 sensitivity and 42.5 specificity).Conclusion ZAGAZIG scale constitutes a validated tool for KOA assessment. ZAGAZIG scale correlated with WOMAC subscales (pain, stiffness and function), VAS and HAQ.